Porous membranes produced by stretching heat-treated sheets of polytetrafluoroethylene and / or modified polytetrafluoroethylene

JP7633816B2Active Publication Date: 2025-02-20CHEMOURS MITSUI FLUOROPRODUCTS CO LTD
View PDF 28 Cites 0 Cited by

Patent Information

Application Number
JP2021014316
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-02-01
Publication Date
2025-02-20
Estimated Expiration
2041-02-01

AI Technical Summary

Benefits of technology

【0022】 本発明は、高耐水性、高強度を必要とする通信機器用の防水通音用途、自動車用のベントフィルター、及び腐食性液体や有機溶剤、或いは半導体製造用途における回路基板のエッチング液等のろ過用途、並びにエッチング液中の有価物の回収等の用途等のほかに、燃料電池、キャパシター、リチウム電池等のセパレーター及びその一部として使用することも可能であり、各種正極と負極の物理的な分離用のセパレーターの一部として用いることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007633816000002
    Figure 0007633816000002
  • Figure 0007633816000003
    Figure 0007633816000003
  • Figure 0007633816000004
    Figure 0007633816000004
Patent Text Reader

Abstract

To provide: a porous membrane comprising polytetrafluoroethylene and / or modified polytetrafluoroethylene, which has a small pore diameter, is hard to break, and is resistant to external forces such as penetration; and a method of manufacturing the same.SOLUTION: The present invention relates to a porous membrane comprising polytetrafluoroethylene and / or modified polytetrafluoroethylene, wherein the bubble point due to isopropyl alcohol in accordance with JIS K3832 is 500 kPa or more, a numerical value obtained by dividing the maximum force until a needle penetrates by the thickness of a test piece is 200 mN / μm or more, based on a needle penetration strength test in accordance with JIS Z1707, the percentage of pore openings in a surface image by electron microscopy is 10 to 30%, and the fiber thickness is 250 nm or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a porous membrane made of polytetrafluoroethylene and / or modified polytetrafluoroethylene, which has a small pore size and high strength, and is particularly resistant to tearing and rupture, and to a method for producing the same. [Background technology]

[0002] Polytetrafluoroethylene (PTFE) is used in various fields due to its excellent heat resistance, chemical resistance, water repellency, weather resistance and low dielectric constant. PTFE can be easily made porous by stretching, so many PTFE porous membranes with various characteristics and their manufacturing methods have been invented.

[0003] Because PTFE porous membranes have high water repellency, they are used in applications such as waterproof, breathable clothing, vent filters for adjusting internal pressure in automobile parts, and waterproof, sound-permeable membranes for communication devices. Waterproof performance is indicated by the numerical value of a water pressure resistance test. For example, a membrane used in a mobile phone that is waterproof to a depth of 100 m is required to withstand a water pressure of 1 MPa. To be able to withstand a water pressure of 1 MPa, the pore size of a membrane needs to be a few tens of nanometers or less. In addition, vent filters used to adjust the internal pressure of automobile parts need to be welded to components that require internal pressure adjustment, and the filter must be strong enough to withstand welding. Furthermore, harsh conditions during vehicle operation, such as dust, dirt, pebbles, and other foreign objects, can come into contact with the membrane at high speeds, damaging the membrane and reducing its waterproofing function. For this reason, a protective cap or lid is sometimes provided on the membrane to prevent such foreign objects from coming into direct contact with the membrane, but if the safety of the automobile is important, this is not perfect, and the membrane itself must also be strong. Furthermore, for waterproof clothing, it is necessary to take into consideration the external force applied to the membrane due to agitation in a washing machine during cleaning, etc., and it is also necessary for the membrane to be tear-resistant. Needless to say, in such fields, the membrane is also required to have strength.

[0004] For dust prevention purposes, they are used in filters for air purifiers or vacuum cleaners, dust-collecting bag filters for garbage incinerators, etc., and air filters for clean rooms in semiconductor manufacturing. In addition, due to the purity of PTFE, i.e., because it produces almost no elution, it is being used as a final filter for producing ultrapure water, replacing conventional ultrafiltration membranes.

[0005] In addition, because of its excellent chemical resistance, it is also used for filtering corrosive liquids, organic solvents, and etching solutions for circuit boards in semiconductor manufacturing, and for recovering valuable materials in etching solutions. In recent years, the integration density of circuits has been increasing in semiconductor manufacturing applications, and since the presence of nano-order particles in the etching solution causes the particles to remain on the wiring of integrated circuits, which reduces the manufacturing yield, there is a demand for a PTFE porous membrane with nano-order pores that can remove nano-order particles in the etching solution. Such a porous membrane must have the strength to withstand the filtration pressure and filtration operation.

[0006] Furthermore, applications of PTFE porous membranes are attracting attention in the energy field, particularly in the production of hydrogen, an alternative energy storage means to electricity, and in the fields of batteries and capacitors. Hydrogen is produced using the electrolysis of water, and porous membranes are used as separators by being inserted between positive and negative electrodes in a concentrated alkaline solution under oxidation-reduction reactions at high temperatures. The electrodes are not smooth, but have some unevenness, and the membrane may be damaged by crystals produced by the electrode reaction. Furthermore, since the membrane is strongly pressed between the electrodes, the membrane may be damaged in the same way as when it is pressed against by a needle-shaped foreign object. In these fields, PTFE porous membranes with high strength are also required. For these reasons, a PTFE porous membrane must not only have small pores, but also be strong enough to withstand tearing and even when pressed against a needle-shaped object. However, it has been difficult to obtain a PTFE porous membrane having high strength and nano-order pore sizes.

[0007] Generally, a PTFE porous membrane is often produced by the following steps. 1. Mix PTFE and an auxiliary (hydrocarbon solvent, etc.). 2. The ratio of cylinder cross-sectional area to outlet cross-sectional area (RR) is increased, and a shear force is applied to the PTFE by extrusion molding, causing it to become fibrous, resulting in a sheet- or bead-shaped extrudate. 3. The obtained extrudate is appropriately rolled with a rolling machine (rolls) or the like to form a sheet, and the hydrocarbon solvent is then evaporated off. 4. The obtained sheet-like material is stretched at high temperature in the extrusion direction (hereinafter sometimes referred to as MD) and in the direction perpendicular to the extrusion direction (hereinafter sometimes referred to as CD), and then baked at a temperature above the melting point of PTFE (342-343°C) to obtain a PTFE porous membrane.

[0008] However, with such a general method, it is difficult to obtain a PTFE porous membrane with small pores, high strength, and tear resistance. This is thought to be because the stretching is performed at a temperature below the melting point of PTFE (342 to 343°C), which generates a lot of fine fibers and does not increase the strength. Another reason is that PTFE stretches well below its melting point, which increases the stretch ratio and increases the porosity. Increasing the stretch ratio has the advantage of increasing the tensile strength because the PTFE molecules are more strongly oriented, but it is often weak against tearing, etc. Therefore, many methods have been proposed for producing PTFE porous membranes, in which a rolled and dried sheet is heated above the melting point of PTFE beforehand and then stretched. Although the sheet is heated above the melting temperature, it may be stretched without being completely sintered, which is sometimes called semi-sintered stretching. It is known that this method produces thick fibers and a membrane with small pores.

[0009] Patent Document 1 specifies a method for measuring the heat of fusion of PTFE crystals, and produces a sheet using a resin with a heat of fusion of 32 J / g or more and less than 47.8 J / g, which is then heated above its melting point, cooled and stretched to obtain a porous membrane with a porosity of 30% or more and a thickness of 50 μm or less. The resin with a heat of fusion of 32 J / g or more and less than 47.8 J / g is mainly a commercially available low molecular weight resin or a commercially available resin whose molecular weight has been reduced by decomposing it with radiation or the like.

[0010] In Patent Document 2, a polyimide film is immersed in a PTFE dispersion to form a PTFE coating film, and a PTFE film is obtained by repeating drying and baking steps, and then the PTFE film is peeled off from the polyimide film and the peeled PTFE film is stretched successively in the CD and MD. The porous film obtained by this method is resistant to needle puncture, with a characteristic value of needle puncture strength of 5 to 15 gf / μm per unit thickness (49 to 147 mN / μm).

[0011] In Patent Document 3, in the process of producing a PTFE porous membrane, one side of the film before stretching is heated to form a temperature gradient in the thickness direction of the film, and the semi-sintered film is successively stretched and heat-set in the extrusion direction (MD) and the direction perpendicular to the extrusion direction (CD), thereby producing a stretched film with high filtration efficiency used for precision filtration of gases, liquids, etc., in which the average pore size continuously decreases in the thickness direction and the average pore size on the heated surface is 0.05 μm to 10 μm, and has an asymmetric structure. There are.

[0012] However, in Patent Document 1, the molecular weight of the resin used is low, and low molecular weight resins often have poor strength, just like general plastic materials. In addition, in Patent Document 2, the needle puncture strength is specified, but it cannot be said that it is sufficiently strong. In Patent Document 3, the strength of the very thin part of the heating surface may be strong, but the film as a whole does not have sufficient strength. Although these conventional techniques are effective in limited applications, they have problems such as insufficient membrane strength in other applications, and are considered insufficient for providing porous membranes having small pore sizes and used under harsher conditions. [Prior art documents] [Patent documents]

[0013] [Patent Document 1] Patent No. 5008850 [Patent Document 2] JP 2018-204006 A [Patent Document 3] Patent No. 4850814 [Patent Document 4] International Publication No. 2016 / 117565 [Patent Document 5] International Publication No. 2007 / 119829 [Patent Document 6] Patent No. 5054007 [Patent Document 7] JP 2018-16697 A [Patent Document 8] U.S. Pat. No. 3,037,953 Summary of the Invention [Problem to be solved by the invention]

[0014] An object of the present invention is to provide a novel porous membrane made of polytetrafluoroethylene and / or modified polytetrafluoroethylene, which has small pores, is resistant to tearing, and is resistant to external forces such as puncture. [Means for solving the problem]

[0015] The present invention provides a porous film made of polytetrafluoroethylene and / or modified polytetrafluoroethylene, characterized in that the bubble point in isopropyl alcohol (IPA) based on JIS K3832 is 500 kPa or more, the maximum force required for a needle to penetrate the film, as determined by a needle puncture strength test based on JIS Z1707, divided by the thickness of a test piece is 200 mN / μm or more, the ratio of open pores in a surface image taken by an electron microscope is 10 to 30%, and the fiber thickness is 250 nm or more.

[0016] In addition to the above, the polytetrafluoroethylene and / or modified polytetrafluoroethylene resin is heated to 365 ° C. at a rate of 10 ° C. / min using a differential scanning calorimeter, cooled to 330 ° C. at a rate of -10 ° C. / min, cooled from 330 ° C. to 305 ° C. at a rate of -1 ° C. / min, further cooled from 305 ° C. to 245 ° C. at a rate of -10 ° C. / min, and then heated to 365 ° C. at a rate of 10 ° C. / min. The heat of fusion between 296 and 343 ° C. is less than 32 J / g. The bubble point is 600 kPa or more, and the value obtained by dividing the maximum force until the needle penetrates by the thickness of the test piece in the needle puncture strength test is 250 mN / μm or more. This is a preferred embodiment of the present invention.

[0017] The present invention also provides a method for producing a porous membrane made of polytetrafluoroethylene and / or modified polytetrafluoroethylene, comprising the steps of: 1. Made of polytetrafluoroethylene and / or modified polytetrafluoroethylene obtaining a sheet or coating that has not been subjected to a heat treatment of 250°C or more; 2. A process of fixing the sheet or coating and heat-treating it so that the ratio (ΔH / ΔH0) of the heat of crystalline fusion (ΔH0) to (ΔH) described below is 1.0 to 2.0, where ΔH0 means the heat of crystalline fusion between 295 and 360°C when a sheet or coating made of polytetrafluoroethylene and / or modified polytetrafluoroethylene resin that has not been subjected to heat treatment of 250°C or more is heated at 360°C for 20 minutes and then cooled at room temperature, and the resulting sheet or coating is heated to 380°C at a rate of 10°C / min, and ΔH means the heat of crystalline fusion between 295 and 360°C when a sheet or coating made of polytetrafluoroethylene and / or modified polytetrafluoroethylene that has not been subjected to heat treatment of 250°C or more is heated to 380°C at a rate of 10°C / min; 3. A step of stretching the heat-treated sheet or coating in one direction and then successively stretching the sheet or coating in a direction perpendicular to the first direction; The present invention provides a method for producing a porous film made of polytetrafluoroethylene and / or modified polytetrafluoroethylene, comprising the steps of:

[0018] Here, the method for producing a porous membrane, in which the heat treatment step is a step of fixing the sheet or the coating film and heat treating the sheet or the coating film so that the ratio (ΔH / ΔH0) of the heat of crystal fusion (ΔH0) to (ΔH) is 1.2 to 1.8, is a preferred embodiment of the present invention.

[0019] A method for producing a porous membrane in which the heat-treated sheet is stretched in the extrusion direction and then successively stretched in the perpendicular direction is also a preferred embodiment of the present invention.

[0020] Furthermore, the method for producing a porous membrane in which the sheet that has not been subjected to the heat treatment at 250°C or more is obtained by mixing polytetrafluoroethylene and / or modified polytetrafluoroethylene with a hydrocarbon solvent having a boiling point of 150-290°C, extruding the mixture with an extruder at RR35-120 and at a molding temperature of room temperature to 120°C, and rolling the sheet-like or bead-like extrudate is a preferred embodiment of the present invention.

[0021] The method for producing a porous membrane, in which the coating film that has not been subjected to the heat treatment at 250°C or more is obtained by applying a dispersion of polytetrafluoroethylene and / or modified polytetrafluoroethylene containing a surfactant, a film-forming agent, and a thickener and having a solid content concentration of 5 to 75 mass% to a flat plate having a heat resistance of 400°C or more so that the thickness after drying is 1 to 50 μm, and then drying at 100 to 150°C for 10 to 20 minutes, is also a preferred embodiment of the present invention. Effect of the Invention

[0022] The present invention can be used as a waterproof sound transmission filter for communication devices that require high water resistance and high strength, as an automobile vent filter, and as a separator or a part thereof for fuel cells, capacitors, lithium batteries, etc., in addition to filtering corrosive liquids, organic solvents, or etching solutions for circuit boards in semiconductor manufacturing applications, and for recovering valuables in etching solutions. It can also be used as a part of a separator for physically separating various positive and negative electrodes. [Brief description of the drawings]

[0023] [Figure 1] Electron microscope photograph of the surface of the PTFE porous membrane of Example 2 (magnification: 10,000 times) [Diagram 2] Binary photograph of the surface of the PTFE porous membrane of Example 2 (magnification: 10,000 times) [Diagram 3] Electron microscope photograph of the surface of the PTFE porous membrane of Comparative Example 2 (magnification: 5000 times) [Figure 4] Binary photograph of the surface of the PTFE porous membrane of Comparative Example 2 (magnification: 5000 times) DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] The PTFE forming the porous membrane of the present invention may be replaced with any other suitable material within the range that does not impair the properties of PTFE. In addition, modified PTFE modified with less than 1% by weight of a comonomer copolymerizable with tetrafluoroethylene (TFE) may be used. An example of such modified PTFE is a copolymer of TFE and a small amount of a monomer other than TFE, as described in Patent Document 5. More specifically, a copolymer of tetrafluoroethylene and less than 1% by weight of at least one monomer copolymerizable with tetrafluoroethylene selected from hexafluoropropylene, perfluoro(alkyl vinyl ether), fluoroalkylethylene, and chlorotrifluoroethylene, which does not have melt moldability, may be used.

[0025] Regarding the PTFE and / or modified PTFE used in the present invention, when the PTFE and / or modified PTFE are heated to 365°C at a rate of 10°C / min using a differential scanning calorimeter, cooled to 330°C at a rate of -10°C / min, cooled from 330°C to 305°C at a rate of -1°C / min, further cooled from 305°C to 245°C at a rate of -10°C / min, and then heated to 365°C at a rate of 10°C / min, if the heat of crystal fusion between 296 and 343°C is less than 32 J / g, this means that the molecular weight of the PTFE is high, and a PTFE stretched film with high strength, i.e., a PTFE porous film with high needle puncture strength, can be obtained, which is more preferable. As with general-purpose plastic materials, the PTFE and / or modified PTFE of the present application can also obtain higher mechanical strength as the molecular weight increases.

[0026] The molecular weight of such PTFE or modified PTFE correlates with the standard specific gravity (SSG) based on ASTM D4895, and the SSG of the PTFE or modified PTFE of the present invention is 2.19 or less, preferably 2.18 or less, and more preferably 2.16 or less, which is suitable for producing a high-strength porous membrane. Examples of these resins that can be used include 660J, 650J, and high molecular weight modified polytetrafluoroethylene manufactured by Mitsui-Chemours Fluoroproducts, F106 and F104 manufactured by Daikin Industries, and CD123E and CD145E manufactured by AGC. The porous membrane made of PTFE or modified PTFE of the present invention is - Bubble point of 500kPa or more based on isopropyl alcohol (IPA) according to JIS K3832 -The maximum force required for the needle to penetrate the test piece in the needle puncture strength test based on JIS Z1707 divided by the thickness of the test piece is 200mN / μm or more. The ratio of open pores is 10-30%, - Fiber thickness is 250nm or more It meets all the requirements.

[0027] The bubble point of the porous membrane of the present invention in isopropyl alcohol (IPA) based on JIS K3832 is 500 kPa or more, preferably 600 kPa or more. A bubble point of 500 kPa or more indicates that the pore size of the PTFE porous membrane is small enough to remove nano-order fine particles. In general, the maximum pore size of a PTFE porous membrane is calculated using the bubble point according to the following formula.

[0028] Maximum pore diameter of PTFE porous membrane (diameter: nm) = 4 × γ × cosΘ / P ×10 9 γ: Surface tension of IPA (Pa m) Θ: Contact angle between IPA and porous membrane (Θ=0) P: Bubble point pressure (Pa)

[0029] When the bubble point is 500 kPa, the maximum pore size calculated by the above formula is about 146 nm, but since there are many pores with diameters of 146 nm or less in the PTFE porous membrane, it is possible to capture particles of several tens of nanometers when filtering liquids. In general, when the bubble point is less than 400 kPa, it is difficult to remove nano-order particles, and the waterproofing is also poor. This is not desirable because it reduces the The PTFE porous membrane of the present invention has a bubble point of 500 kPa or more, so the pore size of the porous membrane is small. And, since the PTFE porous membrane of the present invention has high strength, it does not break even at a water pressure of nearly 100 m in the application of a vent filter or a waterproof sound transmission, and does not cause water leakage.

[0030] The PTFE porous membrane of the present invention shows a value of 200 mN / μm or more in the needle puncture strength test based on JIS Z1707, obtained by dividing the maximum force until the needle penetrates by the thickness of the test piece. The needle puncture strength test based on JIS Z1707 is one of the physical properties required for vent filters and battery separator applications, and is an index that indicates the resistance to tearing and breaking of a porous membrane more than physical properties such as tensile strength. In the present invention, specifically, a semicircular needle with a diameter of 1.0 mm and a tip radius of 0.5 mm as specified in JIS Z1707 is pierced at a test speed of 50±5 mm / min, and the maximum force (mN) until the needle penetrates is divided by the thickness (μm) of the test piece (needle puncture strength) is measured. Since the thicker the membrane, the higher the needle puncture strength, in the present invention, the strength per unit thickness is specified for the purpose of providing a membrane that is thin but difficult to break. The needle puncture strength of the present invention is 200 mN / μm or more, preferably 250 mN / μm or more, and more preferably 300 mN / μm or more. Furthermore, while the above-mentioned Patent Document 2 describes the needle puncture strength as 49 to 146 mN / μm, the PTFE porous membrane of the present invention has a value of 200 mN / μm or more.

[0031] The pore openings (surface opening rate) of the PTFE porous membrane of the present invention are 10 to 30%. The surface opening rate is a physical property value related to the air permeability of the porous membrane, so a higher surface opening rate is preferable, but if it exceeds 30%, the needle puncture strength decreases, which is unpreferable, and if it is less than 10%, the air permeability or liquid permeability (flow rate) decreases (becomes too low), which is unpreferable. The surface opening of the porous membrane of the present invention is generated by the crystal part generated by the heat treatment of the PTFE sheet or coating film in the manufacturing process of the porous membrane being deformed (destroyed) by stretching. This is well known to those skilled in the art of PTFE porous membranes. In the process of recrystallization by heat treatment, the heating temperature, heating time, and the degree of crystal growth by slow cooling (recrystallization degree) affect the opening rate. If the heat treatment is insufficient, it is difficult to obtain a porous membrane with a small pore size, and if the heat treatment is excessive, deformation by stretching is difficult to occur, so the membrane is not made porous.

[0032] The fiber thickness of the PTFE porous membrane of the present invention is 250 nm or more, and preferably 300 nm or more. If the fiber thickness is less than 250 nm, the strength of the PTFE porous membrane cannot be obtained (the strength decreases), which is not preferable. The fibers in the PTFE porous membrane of the present invention are amorphous portions of PTFE (parts in which PTFE molecular chains are not regularly arranged, as opposed to regularly arranged PTFE molecular chains in crystalline portions) formed by the heat treatment in the above-mentioned manufacturing process of the porous membrane, and have a high degree of entanglement of PTFE molecular chains, making them less likely to deform (break) under loads such as shear force during stretching and needle puncture, and are therefore thought to exhibit excellent mechanical strength (needle puncture strength). Such fibers of the present invention are believed to be different from fibers (PTFE molecular chains) that have inferior mechanical strength and are produced by the disintegration of the molecular chains in the PTFE particles when a sheet is stretched that has not been subjected to a heat treatment of 250°C or higher.

[0033] The surface opening ratio and fiber thickness of the PTFE porous membrane of the present invention can be measured by observing the surface of the porous membrane with an electron microscope and directly measuring the dimensions and area from the image. In the present invention, however, it is preferable to use the image software described in Patent Document 4. For example, a method is used in which the porous membrane and voids are color-coded into black and white using image analysis software Image-Pro-Plus manufactured by Media Cybernetic, and the ratio of each is automatically calculated. This allows for simpler and more accurate calculation. This method is called binarization. The electron microscope image used for binarization may be an image taken at a magnification at which pores and fiber structure can be distinguished, and the magnification is not limited. For the porous membrane of the present invention with a small pore size and an IPA bubble point of 500 kPa or more, an electron microscope image at a magnification of 5,000 to 20,000 is preferably used.

[0034] The thickness of the PTFE porous membrane of the present invention is not particularly limited, but a polytetrafluoroethylene porous membrane having a thickness of 70 μm or less is a preferred embodiment of the present invention. The preferred range of the thickness is 50 μm or less, and more preferably 20 μm or less. Next, the method for producing the PTFE porous membrane of the present invention will be described.

[0035] In the present invention, a heat treatment stretching method is used in which an unstretched sheet is heated to above its melting point and then stretched, as described in Patent Document 1. In the normal method of stretching below its melting point and then baking, as described above, the fiber diameter is small and the strength is insufficient, making it impossible to obtain the high needle puncture strength that is the goal of the present invention. As mentioned above, stretching causes the crystals to deform and become porous, but in the heat treatment stretching method adopted in the present invention, the larger the heat of fusion of the crystals of PTFE used in production, the easier it is to stretch and the easier it is to make the pores. PTFE is known to have the property that even if it is heated once to melt the crystals, some of them will recrystallize when cooled, and the higher the heat of fusion of the crystals, the more crystals there are. If the amount of crystals is small, the film will not become porous even when stretched, but conversely, if the amount of crystals is large, not only will a membrane with small pores not be obtained, but the porous membrane will have low needle puncture strength. Regarding this point, Patent Document 1 also describes that the heat of crystal fusion must be 32 J / g or more and less than 47 J / g even when cooled after heating above the melting point.

[0036] However, a resin having such a heat of fusion has a low molecular weight, and it is difficult to prepare a film having high needle puncture strength. In the present invention, a method has been found in which the pore size can be reduced by stretching under specific conditions of heat treatment, and a membrane with high needle puncture strength can be produced. In addition, when PTFE of less than 32 J / g is used, a membrane with higher needle puncture strength can be obtained.

[0037] The details of the method for producing the PTFE porous membrane of the present invention are as follows. The manufacturing method of the present invention involves three main steps: 1. a step of obtaining a sheet or coating film made of PTFE and / or modified PTFE that has not been heat-treated at 250°C or higher, 2. a heat treatment step, and 3. a stretching step. First, 1. the step of obtaining a sheet or coating film made of PTFE and / or modified PTFE that has not been subjected to heat treatment at 250° C. or more, and then 2. the heat treatment step that follows will be described.

[0038] The method for obtaining a sheet or coating film made of PTFE and / or modified PTFE is not particularly limited. First, in order to obtain PTFE and / or modified PTFE, a method generally used in the art can be adopted. In the method using a "sheet", the following method is preferred, which is based on the general manufacturing method of a PTFE porous membrane, and includes adding and mixing polytetrafluoroethylene and / or modified polytetrafluoroethylene powder with a hydrocarbon solvent having a boiling point of 150 to 290°C, extruding the mixture at RR35 to 120 using an extruder to obtain a sheet-like or bead-like extrudate, rolling the extrudate to produce a sheet-like rolled product, and then removing the hydrocarbon solvent.

[0039] The hydrocarbon solvent used in the production of the PTFE porous membrane of the present invention is a linear saturated hydrocarbon solvent and / or a branched saturated hydrocarbon solvent having a boiling point of 150 to 290°C and consisting of at least one type of linear saturated hydrocarbon having 8 to 16 carbon atoms. For example, examples of the linear saturated hydrocarbon solvent include naphtha (a hydrocarbon solvent consisting of at least one type of linear saturated hydrocarbon having 8 to 14 carbon atoms, boiling point 150 to 180°C), Norpar 13 (carbon number 12 to 14, boiling point 222 to 243°C), and Norpar 15 (carbon number 9 to 16, boiling point 255 to 279°C). Examples of the branched saturated hydrocarbon solvent include Isopar G (carbon number 9 to 12, boiling point 160 to 176°C), Isopar H (carbon number 10 to 13, boiling point 178 to 188°C), and Isopar M (carbon number 11 to 16, boiling point 180 to 290°C), all manufactured by Exxon Mobil Corporation. Examples of suitable solvents include SUPERSOLU FP25 (carbon number 11 to 13, boiling point 150°C or higher) manufactured by Idemitsu Kosan Co., Ltd. However, it is preferable to use Isopar M because it prevents evaporation of the solvent during rolling, can be easily removed by heating, and is odorless.

[0040] To facilitate extrusion molding, the hydrocarbon solvent (preferably Isopar M manufactured by ExxonMobil) is added in an amount of 16% by weight to 22% by weight relative to the PTFE, preferably 18% by weight to 20% by weight for ease of extrusion, and mixed for 3 to 5 minutes. The mixture is then left to stand at 20°C or higher for 12 hours or more. The resin is then placed in a cylindrical pressure device and pressurized with a cylinder to expel the air contained in the resin powder and the hydrocarbon solvent, thereby obtaining a cylindrical preform.

[0041] Next, using an extruder, the cylindrical preform is extruded at a RR of 35 to 120, preferably 50 to 120, more preferably 50 to 80, a molding temperature of 40 to 60°C, preferably 40 to 50°C, and a ram extrusion speed of 10 to 60 mm / min, preferably 20 to 30 mm / min, to produce sheet-like extrudates, bead-like extrudates, tubular extrudates, etc. The tubular extrudates can be cut lengthwise with a blade and opened into a sheet shape. When the ram extrusion speed is less than 10 mm / min, the productivity decreases, which is not preferable, and when the extrusion speed exceeds 60 mm / min, the extrusion pressure increases and it becomes difficult to obtain a uniform extrudate, which is also not preferable. If the RR is less than 35, a sufficient shear (shearing force) is not applied to the primary particles of PTFE, so that the primary particles of PTFE are not turned into fibers, and the strength of the extrudate decreases, which is undesirable. Furthermore, as RR is increased, the extrusion pressure during extrusion molding increases, and when RR exceeds 120, a large molding machine becomes necessary, which is undesirable. In addition, if the molding temperature is lower than room temperature, the hydrocarbon solvent and PTFE do not mix well, resulting in a decrease in fluidity, which is not preferred, and if the molding temperature exceeds 120°C, the hydrocarbon solvent evaporates too much, which is not preferred.

[0042] The sheet-like extrudate or the like is rolled in the MD direction using two pairs of rolls to a predetermined thickness. The thickness is rolled to 200 μm or less, preferably 100 μm or less, and more preferably 50 μm or less, but in this method, the limit is 50 to 100 μm. Patent Document 6 also introduces a method for adjusting the ratio of tensile strength in the MD and CD of the rolled sheet by not only rolling the extruded sheet in the MD with a roll but also pulling the sheet in the direction perpendicular to the extrusion direction while still containing an auxiliary. In the present invention, the rolling method is not limited, but a similar method can be adopted to reduce the difference in strength between the MD and CD of the sheet before heat treatment as necessary. That is, for rolling in the MD, the extruded sheet is cut to an appropriate length and then rolled in the MD. For the subsequent rolling in the CD, the sheet that has been rolled in the MD is rotated 90 degrees with respect to the MD and then deformed into the CD. By combining rolling in these two directions, the sheet-like extrudate or the like is rolled to 400 μm or less, preferably 300 μm or less, more preferably 200 μm or less to obtain a sheet-like rolled product.

[0043] The hydrocarbon solvent in the sheet-like rolled product is evaporated and removed at 150° C. or higher, preferably 200° C. or higher, for 5 minutes or longer, preferably 15 minutes or longer, to obtain a rolled sheet that has not been subjected to a heat treatment at 250° C. or higher. Next, this sheet is heated at 360°C for 20 minutes, cooled to room temperature, and then heated to 380°C at a rate of 10°C / min, and the heat of crystal fusion between 295 and 360°C is measured and this is defined as ΔH0. Next, the heat of crystal fusion is measured under the same conditions except that only the heating temperature and heating time are changed, and when this is defined as ΔH, the heating temperature and heating time are determined so that the value of ΔH / ΔH0 is 1.0 to 2.0. The temperature of such heat treatment must be equal to or higher than the melting point of PTFE. The value of ΔH / ΔH0 is preferably 1.2 to 1.8, more preferably 1.2 to 1.6. The heat treatment is carried out by fixing the sheet made of PTFE and / or modified PTFE so as to prevent dimensional change. The above heat treatment step is similarly applied to the heat treatment step for the coating film described below. The rolled sheet obtained by the above method, which has not been subjected to heat treatment at 250°C or more, can be continuously passed through a heating furnace and heat-treated to a range of ΔH / ΔH0 of 1.0 to 2.0. It can also be cut to a predetermined area and heat-treated in a high-temperature dryer. The conditions for the heat treatment cannot be generally specified because the conditions for baking vary depending on the type of resin. However, in the case of general PTFE or modified PTFE, the ΔH / ΔH0 value can be set to a range of 1.0 to 2.0 by heating for about 30 to 500 seconds at a temperature of 400°C, preferably 350 to 400°C, more preferably 350 to 385°C, from the melting point of the PTFE or modified PTFE used.

[0044] Next, the method using a "coating film" will be described. This method is a method in which a dispersion is applied to a flat plate in accordance with Patent Document 7. A suitable method is to add a surfactant, a water-soluble polymer as a thickener, and an organic solvent to a dispersion having a solid content concentration of 5 to 75 mass%, preferably 40 to 65 mass%, which consists of polytetrafluoroethylene and / or modified polytetrafluoroethylene having an average particle size of 0.01 to 5.00 μm, preferably 0.10 to 1.00 μm, and more preferably 0.10 to 0.50 μm, and then coat the dispersion on a smooth plate having a thickness of 1 mm or more and a heat resistance of 400°C or higher. After drying to remove moisture, the mixture is heated at a temperature of 360°C or higher to decompose and remove the additives, and then cooled to room temperature and peeled off from the smooth plate to produce a coating film. The dispersion to which the surfactant, film-forming agent, water-soluble polymer as a thickener, and organic solvent have been added has a viscosity measured by a B-type viscometer (viscosity at 30 rpm using a No. 2 rotor) of 1 to 600 cps, preferably 100 to 600 cps, and more preferably 200 to 500 cps.

[0045] Examples of surfactants to be added to the dispersion include polyoxyethylene alkyl ether and polyoxyethylene alkyl phenyl ether nonionic surfactants such as LEOCOL manufactured by Lion Corporation, TRITON and TERGITOL series manufactured by Dow Chemical Company, and Emulgen manufactured by Kao Corporation; sulfosuccinates, sodium alkyl ether sulfonates, and mono-long-chain alkyl sulfate anionic surfactants such as REPARL manufactured by Lion Corporation, EMAL and PEREX manufactured by Kao Corporation; polycarboxylates and acrylate-based polymeric surfactants such as REOAR manufactured by Lion Corporation and OROTAN manufactured by Dow Chemical Company. Examples of film-forming agents include polymeric film-forming agents such as polyamide, polyamideimide, acrylic, and acetate, higher alcohols, ethers, and polymeric surfactants having film-forming effects. Examples of thickeners that can be added include water-soluble celluloses, solvent dispersion thickeners, sodium alginate, casein, sodium caseinate, xanthan gum, polyacrylic acid, and acrylic acid esters.

[0046] As the dispersion, a dispersion immediately after polymerization may be used. It is preferable to use a dispersion liquid that has been concentrated and stabilized by a known technique such as the method described in. The concentration of the dispersion is preferably 5 to 75% by mass, and it is preferable to use a dispersion liquid that has been concentrated to increase the concentration of the PTFE resin to 40 to 70% by mass. As described above, the resin is more preferably a resin having a molecular weight of less than 32 J / g (medium to high molecular weight resin) as described in Patent Document 1.

[0047] Next, the dispersion containing the surfactant, film-forming agent, water-soluble polymer as a thickener, and organic solvent is applied to a stainless steel plate, aluminum plate, polyimide film, or glass plate having a heat resistance of 400°C or more, and then heated to about 100°C to dry off the moisture. In the present invention, the coating method is not limited, but a method of spraying using a spray nozzle to dry off the moisture, a method of immersing a plate in the dispersion containing the surfactant, film-forming agent, water-soluble polymer as a thickener, and organic solvent, and then lifting it at a predetermined speed and then drying it, etc. are preferably used. The coating thickness is freely controlled by the viscosity of the dispersion, the number of sprays, the amount of spraying, the lifting speed, etc. In the coating process, it is also possible to continuously coat a polyimide film or aluminum plate, and the speed and the length of the oven can be adjusted so that the plate stagnates for a long time in the hot air drying oven. The desired coating film can also be obtained by coating a glass plate or aluminum plate of a predetermined area and heat-treating it in a high-temperature drying oven.

[0048] Subsequently, the additives are decomposed and removed at a temperature of 360°C or higher. If the heating temperature is low, the coating film will be colored due to the influence of the carbonized additives, so heating is required until it becomes completely white. The heating temperature varies depending on the type of additive, but it is necessary to heat to a temperature of 400°C or higher than the melting point of the PTFE or modified PTFE used, preferably 350 to 400°C, and more preferably 350 to 385°C. Furthermore, the heating time needs to be determined by checking the degree of decomposition and removal, but it is preferable to heat for at least 20 minutes. After heating, the coating film is cooled to room temperature, and a porous film is produced in a stretching process. Note that since the coating film cooled to room temperature has already been heated to a temperature above the melting point, no additional heat treatment is required. It should be noted that under these conditions, the coating film may not be considered to be in a heat-treated state, but rather as a completely baked coating film. However, in the present invention, regardless of the heat treatment, ΔH is measured, the ratio to ΔH0 is calculated, and if ΔH / ΔH0=1.0 to 2.0, it is defined as heat treatment.

[0049] Regarding the preparation of the heat-treated sheet or coating film used in the method for producing a porous film made of PTFE and / or modified PTFE of the present invention, a method of preparing a sheet by mixing PTFE resin with a hydrocarbon solvent, extruding, rolling, and drying, and a method of preparing a coating film by applying a dispersion of PTFE resin to prepare a thin porous film and decomposing and removing additives at the same time as the heat treatment, were specifically introduced. In the present invention, the preparation of the heat-treated sheet or coating film is not particularly limited, but these two methods are preferably used. Furthermore, although high-temperature drying was introduced as a heating means for performing the heat treatment, the heating means is not limited thereto, and a method of contacting a surface heated to above the melting point, including heating with an infrared heater and a heating roll, can also be used in the present invention.

[0050] Finally, the stretching step 3 will be described. In the stretching step, the heat-treated sheet obtained as described above is stretched in one direction in an atmosphere of 150 to 320°C, preferably 300°C, and then successively stretched in the perpendicular direction to the one direction to produce a porous membrane. In the method of stretching a sheet that has not been subjected to the heat treatment process of 2, the direction of stretching is determined to some extent at first, and stretching is generally performed from the direction of extrusion. However, in the heat treatment stretching method adopted in the present invention, stretching can be performed from any direction. In particular, for sheets produced using dispersion coating or sheets produced by the method introduced in Patent Document 6 that have no difference in strength between MD and CD, no matter which direction stretching is started, a porous membrane can be produced. When the stretched porous film needs to be heat-set, it may be baked at a temperature of from the melting point of PTFE to 400° C., preferably 350 to 400° C., more preferably 350 to 385° C., for 10 to 120 seconds.

[0051] In the stretching step for obtaining a PTFE porous membrane, a discontinuous stretching method in which the sheet-like rolled product subjected to step 2 is stretched discontinuously (batchwise) and a continuous stretching method are used. In the present invention, a PTFE porous membrane can be obtained by appropriately selecting a stretching method and a stretching device according to the desired properties of the PTFE porous membrane. The ratio of the stretch ratios in MD and CD of the sheet-like rolled product that has been subjected to the step 2 is difficult to stretch compared to the sheet-like rolled product that has not been heat-treated, so the stretch ratios in MD and CD are limited to 5 to 7 times. In addition, it is not necessary to make the stretch ratios in MD and CD the same, and the stretch ratios in each direction can be determined according to the purpose. The discontinuous (batch type) stretching method is a method in which a sheet-like rolled product that has been heat-treated at a temperature equal to or higher than the melting point is cut and successively stretched using a biaxial stretching machine.

[0052] In the continuous stretching method, first, the sheet-like rolled product subjected to the step 2 is continuously stretched in the same direction as the extrusion direction (MD) of the sheet-like rolled product subjected to the step 2 by changing the speed of each pair of rolls using a longitudinal (extrusion direction) stretching device having multiple pairs of rolls (nip rolls) that can be heated and nipped (squeezed) from above and below. When continuous stretching in the extrusion direction (MD) is performed using multiple pairs of rolls, it is preferable to provide a speed difference between the rotation speeds of each pair of rolls. More specifically, the rotation speed of the second and subsequent pairs of rolls is made faster than the rotation speed of the first pair of rolls in the traveling direction, and the longitudinal stretching is completed between them, and the ratio of the rotation speeds becomes the stretching ratio. When three or more pairs of rolls are used, it is also preferable to perform longitudinal stretching by increasing the speed in the traveling direction (continuous stretching in the extrusion direction (MD)). The diameter of the roll is not limited, but is generally about 200 mm Φ. A method of continuous stretching in the extrusion direction (MD) using an apparatus equipped with a heating furnace between each pair of rolls is also preferably used. Next, using a tenter capable of continuously stretching in the direction perpendicular to the extrusion direction (CD), both sides of the sheet-like stretched material continuously stretched in the extrusion direction (MD) are gripped with chucks, and the chucks are moved while heating, thereby continuously stretching the material in the direction perpendicular to the extrusion direction (CD) to obtain a PTFE porous membrane. EXAMPLES

[0053] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0054] (Standard specific gravity (SSG)) The standard specific gravity of PTFE was determined according to ASTM D4895.

[0055] (heat of crystal fusion) The heat of crystal fusion was measured using a differential scanning calorimeter (Diamond DSC, manufactured by PerkinElmer). 1.PTFE or modified PTFE 10 mg of PTFE or modified PTFE with no heating history of 250°C or higher was heated to 365°C at a rate of 10°C / min, cooled to 330°C at a rate of -10°C / min, cooled from 330°C to 305°C at a rate of -1°C / min, and further cooled from 305°C to 245°C at a rate of -10°C / min, and then heated to 365°C at a rate of 10°C / min. The heat of crystalline fusion between 296 and 343°C was determined. 2.Sheets or coatings ΔH0: A PTFE or modified PTFE sheet or coating that has no heating history of 250°C or higher is heated at 360°C for 20 minutes and then cooled at room temperature to obtain a sheet or coating. 10 mg of the resulting sheet or coating is heated to 380°C at a rate of 10°C / min. From the obtained DSC curve, the heat of crystalline fusion (J / g) at 295 to 360°C is determined. ΔH: A sheet or coating made of polytetrafluoroethylene and / or modified polytetrafluoroethylene that has not been heat-treated at 250°C or higher is heat-treated so that the ratio (ΔH / ΔH0) of the heat of crystalline fusion (ΔH0) to (ΔH) is 1.0 to 2.0. 10 mg of the sheet obtained is heated to 380°C at a rate of 10°C / min, and the heat of crystalline fusion (J / g) between 295 and 360°C is determined.

[0056] (IPA Bubble Point) The bubble point was measured with isopropyl alcohol (IPA) using Porolux1000 manufactured by Microtrackbell in accordance with JIS K3832.

[0057] (Tensile strength (tensile strength) and breathability (Gurley value)) Using a porous membrane sample piece prepared from the PTFE porous membrane obtained under the conditions shown in Table 1, the tensile strength (tensile strength) was measured at 25°C, chuck interval 22mm, and pulling speed 200mm / min using Orientec's Tensilon RTC1310A in accordance with JIS K6251. For the MD (extrusion direction) strength, a porous membrane sample piece of MD50mm×CD10mm was used, and for the CD (direction perpendicular to the extrusion direction) strength, a porous membrane sample piece of MD10mm×CD50mm was used. In addition, MD strength×CD strength is an index showing the strength of the entire PTFE porous membrane, and the larger the value, the better the strength. The air permeability was measured using a Gurley densometer (air permeability tester) manufactured by Toyo Seiki Seisakusho.

[0058] (Ratio of openings in PTFE porous membrane (surface porosity), fiber diameter) The PTFE porous membrane was sputter-deposited with a platinum-palladium alloy and then observed under an electron microscope (SU-8000, manufactured by Hitachi High-Technologies Corporation). In the examples, the surface structure was observed at 10,000 times magnification and binarized using image analysis software Image-Pro-Plus manufactured by Media Cybernetic, and the pore opening rate of the pores of the porous membrane was calculated. The fiber diameter was measured using the software Phenom World's ProX tabletop scanning electron microscope. TM Analysis was performed using Fibermetric in the Pro Suite.

[0059] (Film thickness) The thickness was measured using a dial thickness gauge manufactured by Peacock.

[0060] (Needle puncture test (needle puncture strength)) A semicircular needle with a diameter of 1.0 mm and a tip radius of 0.5 mm as specified in JIS Z1707 was pierced at a test speed of 50±5 mm / min, and the maximum force (mN) until the needle penetrated was divided by the thickness (μm) of the test piece to measure the needle piercing strength.

[0061] (Polymerization of PTFE used in Example 1) In a 4-liter stainless steel (SUS316) autoclave equipped with a stirring blade and a temperature-control jacket, 60 g of paraffin wax, 2300 ml of deionized water, 12 g of the ammonium salt of fluoromonoether acid (formula C3F7-O-CF(CF3)COOH) and 12 g of the ammonium salt of fluoropolyether acid (C3F7-O-[CF(CF3)CF2] n 0.05g of ammonium salt of -CF(CF3)COOH), 0.75g of succinic acid, 0.026g of oxalic acid, and 0.01g of zinc chloride were charged, and the system was replaced with nitrogen gas three times while heating to 80°C to remove oxygen, and then evacuated. Then, 1g of perfluorobutylethylene was added, and the internal pressure was increased to 2.75 MPa with tetrafluoroethylene (TFE), and 1 The internal temperature was maintained at 63°C while stirring at 11 rpm.

[0062] Next, 510 ml of an aqueous solution in which 40 mg of potassium permanganate (KMnO4) was dissolved in 2000 ml of water was pumped in. When the injection of potassium permanganate was completed, the internal temperature was raised to 85°C, and TFE was continued to be fed. When the consumption of TFE reached 740 g, stirring was stopped. The gas in the autoclave was released to normal pressure, a vacuum was drawn, and the pressure was returned to normal pressure with nitrogen gas, after which the contents were taken out and the reaction was terminated. The solid content of the obtained PTFE dispersion was 28%, and the average particle size of the primary particles was 0.24 μm. Next, the obtained dispersion was diluted with water until the solid content was 15%, and mechanical stirring was continued at room temperature until the secondary particles aggregated by mechanical stirring were separated. The resulting aggregated secondary particles (PTFE powder) were dried at 190° C. for 11 hours to obtain a PTFE fine powder. The standard specific gravity (SSG) and heat of crystal fusion defined in Patent Document 1 of the obtained PTFE fine powder are shown in Table 1.

[0063] Example 1 The PTFE fine powder was used, and the amount of Isopar M manufactured by Exxon Mobil Corp. shown in Table 1 was added, and the mixture was mixed for 5 minutes using a Turbula shaker manufactured by Willy A. Bachofen AG. After standing at 25°C for 24 hours, the mixture was placed in a cylinder of a diameter of 80 mmΦ of a preformer, and the cylinder was covered with a lid. The mixture was compression molded at room temperature (about 15 to 30°C) at a speed of 50 mm / min to obtain a cylindrical preform. The obtained preform was extruded using an extruder with RR36, molding temperature of 50°C, and extrusion speed of 20 mm / min using an extrusion die (thickness 1 mm x width 140 mm) to obtain a sheet-like extrudate. The obtained sheet-like extrudate was cut to a length of 250 mm, and rolled multiple times in the extrusion direction (MD) and the direction perpendicular to the extrusion direction (CD) with two sets of rolls heated to 50°C until the thickness after rolling shown in Table 1 was obtained. Thereafter, the Isopar M was evaporated and removed at 200° C. for 15 minutes to obtain a sheet-like rolled product, which was then cut into a square (120 mm square). The four corners of the obtained sheet were fixed to a 1 mm thick aluminum plate (100 mm square) and heat-treated using a high-temperature dryer at the temperature and time shown in Table 1. After heating, it was cooled to room temperature and ΔH and ΔH0 were measured. The temperature and time of the heat treatment are shown in Table 1.

[0064] The stretching was performed using a biaxial stretching device (EX10-S5 model manufactured by Toyo Seiki Seisakusho Co., Ltd.). The periphery of the square (90 mm square) heat-treated sheet was fixed with a chuck (size excluding the chuck gripping margin of the biaxial stretching device: 72 mm square), and the sheet was successively stretched twice in MD and CD at a molding temperature of 300°C and a stretching speed (speed at which the chuck was moved) of 4.32 m / min to obtain a stretched product (PTFE porous membrane) (batch type). The physical properties of the obtained PTFE porous membrane are shown in Table 1. Table 1 also shows the heat of fusion and ΔH / ΔH0 of the resin under specified conditions.

[0065] (Examples 2 and 3) In Example 2, a sheet was produced under the same conditions as in Example 1, except that PTFE resin 650J manufactured by Mitsui-Chemours Fluoroproducts was used and the heating time shown in Table 1 was used. In Example 3, a sheet was produced under the same conditions as in Example 1, except that PTFE resin 660J manufactured by Mitsui-Chemours Fluoroproducts was used and the heating time shown in Table 1 was used. The physical properties of the PTFE porous membranes obtained in Examples 2 and 3 are shown in Table 1. Table 1 also shows the heat of fusion and ΔH / ΔH0 of the resin under specified conditions. 1 and 2 show a photograph of the surface of the PTFE porous membrane obtained in Example 2 observed with an electron microscope at 10,000 magnifications, and a photograph obtained by binarizing this image.

[0066] Example 4 The resin used was PTFE resin 650J manufactured by Mitsui Chemours Fluoro Products. A glass plate (10cm x 10cm) whose surface had been cleaned of oil with an isopropyl alcohol-containing Kimwipe was immersed in a PTFE dispersion (PTFE specific gravity 2.16, average particle size 0.25μm) containing a thickener dispersion type thickener (decomposition temperature less than 380℃), an acrylic film-forming agent (decomposition temperature less than 380℃), and a nonionic surfactant (Lion Corporation's Leocol TDN90-80, decomposition temperature 300℃ or less) with a viscosity of 418cps and a solid content concentration of 65% by mass, and was then pulled up vertically at a pulling speed of 10mm / sec, dried at 120℃ for 15 minutes, and then heat-treated at 380℃ for 60 minutes to obtain a coating film with a thickness of 35μm. The coating film was then peeled off from the glass plate. The peeled coating film was stretched under the same conditions as in Example 1 to obtain a stretched product (PTFE porous membrane). The physical properties of the obtained PTFE porous membrane are shown in Table 1. Table 1 also shows the heat of fusion and ΔH / ΔH0 of the resin under specified conditions.

[0067] Example 5 A stretched product (PTFE porous membrane) was obtained by stretching under the same conditions as in Example 3, except for the stretch ratio shown in Table 1. The physical properties of the obtained PTFE porous membrane are shown in Table 1. Table 1 also shows the heat of fusion and ΔH / ΔH0 of the resin under specified conditions.

[0068] Comparative Example 1 The sheet-like rolled product was molded using PTFE resin 650J manufactured by Mitsui-Chemours Fluoroproducts, and without undergoing a heat treatment process, it was successively stretched twice in MD and CD at a molding temperature of 300°C and a stretching speed (chuck movement speed) of 4.32 m / min to obtain a stretched product (PTFE porous membrane) (batch method). The physical properties of the obtained PTFE porous membrane are shown in Table 1. Table 1 also shows the heat of fusion and ΔH / ΔH0 of the resin under specified conditions.

[0069] Comparative Example 2 The sheet-like rolled product was molded using PTFE resin 650J manufactured by Mitsui-Chemours Fluoroproducts, and without undergoing a heat treatment process, it was successively stretched 10 times in MD and CD at a molding temperature of 300°C and a stretching speed (chuck movement speed) of 4.32 m / min to obtain a stretched product (batch method). The physical properties of the obtained PTFE porous membrane are shown in Table 1. Table 1 also shows the heat of fusion and ΔH / ΔH0 of the resin under specified conditions. 3 and 4 show a photograph of the surface structure of the porous membrane obtained in Comparative Example 2 observed with an electron microscope at 5000 magnifications, and a binarized photograph of this image.

[0070] Comparative Example 3 A stretched product (PTFE porous membrane) was obtained by stretching under the same conditions as in Example 1, except for the heating time shown in Table 1. The physical properties of the obtained PTFE porous membrane are shown in Table 1. Table 1 also shows the heat of fusion and ΔH / ΔH0 of the resin under specified conditions.

[0071] Comparative Example 4 A stretched product (PTFE porous membrane) was obtained under the same conditions as in Example 3, except for the heating time shown in Table 1. The physical properties of the obtained PTFE porous membrane are shown in Table 1. Table 1 also shows the heat of fusion and ΔH / ΔH0 of the resin under specified conditions.

[0072] Comparative Example 5 A stretched product (PTFE porous membrane) was obtained under the same conditions as in Example 3, except for the heating time shown in Table 1. The physical properties of the obtained PTFE porous membrane are shown in Table 1. Table 1 also shows the heat of fusion and ΔH / ΔH0 of the resin under specified conditions.

[0073] The present invention provides a porous membrane having a small pore size, high needle puncture strength, and high tensile strength. It becomes possible to do so. By stretching the film after heat treatment, it is possible to produce a film that is much stronger than conventional stretched films.

[0074] [Table 1] [Industrial Applicability]

[0075] INDUSTRIAL APPLICABILITY The present invention provides a porous membrane made of polytetrafluoroethylene and / or modified polytetrafluoroethylene, which has small pores, is resistant to tearing, and is resistant to external forces such as puncture, and a method for producing the same. The present invention can be used as a separator or a part thereof for fuel cells, capacitors, lithium batteries, etc., in addition to waterproof sound transmission applications for communication devices that require high water resistance and high strength, vent filters for automobiles, and applications such as filtering corrosive liquids, organic solvents, or etching solutions for circuit boards in semiconductor manufacturing applications, and recovery of valuables in etching solutions. It can also be used as a part of a separator for physically separating various positive and negative electrodes.

Claims

1. A porous membrane made of polytetrafluoroethylene and / or modified polytetrafluoroethylene, The polytetrafluoroethylene and / or the modified polytetrafluoroethylene has a heat of fusion of less than 32 J / g between 296 and 343°C when the polytetrafluoroethylene and / or the modified polytetrafluoroethylene is heated to 365°C at a rate of 10°C / min using a differential scanning calorimeter, cooled to 330°C at a rate of -10°C / min, cooled from 330°C to 305°C at a rate of -1°C / min, further cooled from 305°C to 245°C at a rate of -10°C / min, and then heated to 365°C at a rate of 10°C / min, The bubble point based on isopropyl alcohol according to JIS K3832 is 600 kPa or more, The maximum force required for a needle to penetrate the test piece in a needle puncture strength test based on JIS Z1707 divided by the thickness of the test piece is 250 mN / μm or more. The ratio of the open pores is 10 to 30%, and The fiber thickness is 250 nm or more.

1. A porous membrane made of polytetrafluoroethylene and / or modified polytetrafluoroethylene.

2. A method for producing a porous membrane made of the polytetrafluoroethylene and / or modified polytetrafluoroethylene according to claim 1, comprising the steps of: (1) a step of obtaining a sheet or coating film made of polytetrafluoroethylene and / or modified polytetrafluoroethylene that has not been subjected to a heat treatment at 250°C or more; (2) a step of fixing the sheet or coating film and heat-treating it so that the ratio (ΔH / ΔH) of the heat of crystal fusion (ΔH0) to (ΔH) described below is 1.0 to 2.0; Where: ΔH0: the heat of crystal fusion between 295 and 360° C. when a sheet or coating film made of polytetrafluoroethylene and / or modified polytetrafluoroethylene resin that has not been subjected to heat treatment of 250° C. or more is heated at 360° C. for 20 minutes and then cooled at room temperature to obtain a sheet or coating film, which is then heated to 380° C. at a rate of 10° C. / min. ΔH: Polytetrafluoroethylene and / or modified polytetrafluoroethylene The heat of crystal fusion between 295 and 360°C when a sheet or coating film that has not been subjected to heat treatment at 250°C or higher is heated to 380°C at a rate of 10°C / min after heat treatment. means; (3) stretching the heat-treated sheet or coating in one direction and then successively stretching the sheet or coating in a direction perpendicular to the first direction; A method for producing a porous membrane comprising the steps of:

3. The heat treatment step (2) fixes the sheet or coating film of the (1) and heats it so that the ratio (ΔH / ΔH) of the heat of crystal fusion (ΔH0) to (ΔH) is 1.2 to 1.

8. The method for producing a porous membrane according to claim 2, further comprising the step of treating the porous membrane.

4. The method for producing a porous membrane according to claim 2 or 3, wherein in the stretching step (3), the sheet heat-treated in the heat treatment step (2) is stretched in the extrusion direction and then successively stretched in the perpendicular direction.

5. The method for producing the porous membrane according to any one of claims 2 to 4, wherein the sheet used in the step (1) is obtained by mixing polytetrafluoroethylene and / or modified polytetrafluoroethylene with the hydrocarbon solvent having the boiling point of 150 to 290 ° C, extruding the mixture with extruder at RR35 to 120 and at the molding temperature of room temperature to 120 ° C, and rolling the sheet-like or bead-like extrudate obtained.

6. The method for producing the porous membrane according to claim 2 or 3, wherein the coating film used in the step (1) is obtained by applying a dispersion of polytetrafluoroethylene and / or modified polytetrafluoroethylene with a solid content concentration of 5-75 mass% containing surfactant, film-forming agent and thickener to a flat plate having a heat resistance of 400°C or higher so that the thickness after drying is 1-50 μm, and then drying at 100-150°C for 10-20 minutes.

Citation Information

Patent Citations

  • JP1973050814A

  • JP1975008850A

  • JP1975054007A

  • Production of multilayered porous membrane of polytetrafluoroethylene

    JP1991179039A

  • Production of porous body

    JP1993032810A